Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.

An Assessment of Demersal Elasmobranch Occurrence and Associated Habitats Using an Autonomous Underwater Vehicle ( AUV ) - Jonathon Taylor; John A. Howe; James Thorburn; Clive J. Fox; Christopher McGonigle; Petra Rybanska (Marine Ecology, 2025)
To implement effective management and conservation strategies, an understanding of the spatial ecology, habitat preferences and movement of demersal elasmobranchs is required. This study combines a photographic survey obtained from an autonomous underwater vehicle (AUV) with existing bathymetric data to help understand elasmobranch ecology within the Firth of Lorn, western Scotland. This area is within the Loch Sunart to Sound of Jura Marine Protected Area (MPA) and designated for the protection of the critically endangered flapper skate ( Dipturus intermedius ). Two areas of seabed were surveyed using an AUV in water depths of 110–165 m southwest of the Isle of Kerrera. Eight surveys were conducted in total, four in each area. Each area was surveyed twice over 2 days in October 2020 and twice in 2 days in May June 2021. One day used bait on the seabed (October) whilst all the others had no bait. For each survey, the AUV travelled 17 km at a height of 2 m above the seabed in a lawnmower pattern providing 0.5 km 2 photographic coverage for ~2 h per survey. Five elasmobranch species, two scyliorhinids ( Scyliohinus canicula and Galeus melastomus ) and three rajiformes ( D. intermedius , Raja clavata and Leucoraja naevus ), were identified from a total of 43 k seabed photographs. In total 42 individual animals and 7 egg cases were observed. Although the AUV had short survey times and small study areas the results are encouraging for AUVs being a useful tool in understanding elasmobranch ecology.

Dinoflagellate chloroplasts as a model for extreme genome reduction and fragmentation in organelles – The COCOA principle for gene retention - Christopher J. Howe; Adrian C. Barbrook (Protist, 2024)

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

25 years of Protist: A thank you to Editor-in-Chief Michael Melkonian - R. Ellen R. Nisbet; Christopher J. Howe (Protist, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A dual compartment cuvette system for correcting scattering in whole-cell absorbance spectroscopy of photosynthetic microorganisms - John R. D. Hervey; Paolo Bombelli; David J. Lea-Smith; Alan K. Hulme; Nathan R. Hulme; Atvinder K. Rullay; Robert Keighley; Christopher J. Howe (Photosynthesis Research, 2022)
Absorption spectroscopy is widely used to determine absorption and transmission spectra of chromophores in solution, in addition to suspensions of particles, including micro-organisms. Light scattering, caused by photons deflected from part or all of the cells or other particles in suspension, results in distortions to the absorption spectra, lost information and poor resolution. A spectrophotometer with an integrating sphere may be used to alleviate this problem. However, these instruments are not universally available in biology laboratories, for reasons such as cost. Here, we describe a novel, rapid, and inexpensive technique that minimises the effect of light scattering when performing whole-cell spectroscopy. This method involves using a custom made dual compartment cuvette containing titanium dioxide in one chamber as a scattering agent. Measurements were conducted of a range of different photosynthetic micro-organisms of varying cell size and morphology, including cyanobacteria, eukaryotic microalgae and a purple non-sulphur bacterium. A concentration of 1 mg ml −1 titanium dioxide, using a spectrophotometer with a slit width of 5 nm, produced spectra for cyanobacteria and microalgae similar (1–4% difference) to those obtained using an integrating sphere. The spectrum > 520 nm was similar to that with an integrating sphere with the purple non-sulphur bacterium. This system produced superior results to those obtained using a recently reported method, the application of the diffusing agent, Scotch™ Magic tape, to the side of the cuvette. The protocol can be completed in an equivalent period of time to standard whole-cell absorbance spectroscopy techniques, and is, in principle, suitable for any dual-beam spectrophotometer.

Performance determinants, running energetics and spatiotemporal gait parameters during a treadmill ultramarathon - Christopher C. F. Howe; Nicola Swann; Owen Spendiff; Anna Kosciuk; Elizabeth K. L. Pummell; Hannah J. Moir (European Journal of Applied Physiology, 2021)
Purpose The objective of this study was to investigate the changes in metabolic variables, running energetics and spatiotemporal gait parameters during an 80.5 km treadmill ultramarathon and establish which key predictive variables best determine ultramarathon performance. Methods Twelve participants (9 male and 3 female, age 34 ± 7 years, and maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max ) 60.4 ± 5.8 ml·kg −1 ·min −1 ) completed an 80.5 km time trial on a motorised treadmill in the fastest possible time. Metabolic variables: oxygen consumption ( $$\dot{V}$$ V ˙ O 2 ), carbon dioxide production ( $$\dot{V}$$ V ˙ CO 2 ) and pulmonary ventilation ( $$\dot{V}$$ V ˙ E ) were measured via indirect calorimetry every 16.1 km at a controlled speed of 8 km·h −1 and used to calculate respiratory exchange ratio (RER), the energy cost of running (Cr) and fractional utilisation of $$\dot{V}$$ V ˙ O 2max ( F ). Spatiotemporal gait parameters: stride length (SL) and cadence (SPM) were calculated via tri-axial accelerometery. Results Trial completion time was 09:00:18 ± 01:14:07 (hh:mm:ss). There were significant increases in $$\dot{V}$$ V ˙ O 2 , Cr, F , $$\dot{V}$$ V ˙ E and heart rate (HR) ( p < 0.01); a significant decrease in RER ( p < 0.01) and no change in SL and SPM ( p > 0.05) across the measured timepoints. F and Cr accounted for 61% of the variance in elapsed finish time ( $$R_{{{\text{adj}}}}^{{2}}$$ R adj 2 = 0.607, p < 0.01). Conclusion A treadmill ultramarathon elicits significant changes in metabolic variables, running energetics and spatiotemporal gait parameters. With F and Cr explaining 61% of variance in finish time. Therefore, those able to maintain a higher F , while adopting strategies to minimise an increase in Cr may be best placed to maximise ultramarathon performance.

Influence of Local, Landscape, and Regional Variables on Sedge and Marsh Wren Occurrence in Great Lakes Coastal Wetlands - Hannah G. Panci; Gerald J. Niemi; Ronald R. Regal; Douglas C. Tozer; Thomas M. Gehring; Robert W. Howe; Christopher J. Norment (Wetlands, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Diversity of transcripts and transcript processing forms in plastids of the dinoflagellate alga Karenia mikimotoi - Richard G. Dorrell; George A. Hinksman; Christopher J. Howe (Plant Molecular Biology, 2016)

Derek Bendall (1930–2014) - Christopher J. Howe; Peter R. Rich; Marcellus Ubbink (Photosynthesis Research, 2015)

Assessing S ymbiodinium diversity in scleractinian corals via next‐generation sequencing‐based genotyping of the ITS2 rDNA region - Chatchanit Arif; Camille Daniels; Till Bayer; Eulalia Banguera‐Hinestroza; Adrian Barbrook; Christopher J. Howe; Todd C. LaJeunesse; Christian R. Voolstra (Molecular Ecology, 2014)
The persistence of coral reef ecosystems relies on the symbiotic relationship between scleractinian corals and intracellular, photosynthetic dinoflagellates in the genus Symbiodinium . Genetic evidence indicates that these symbionts are biologically diverse and exhibit discrete patterns of environmental and host distribution. This makes the assessment of Symbiodinium diversity critical to understanding the symbiosis ecology of corals. Here, we applied pyrosequencing to the elucidation of Symbiodinium diversity via analysis of the internal transcribed spacer 2 ( ITS 2) region, a multicopy genetic marker commonly used to analyse Symbiodinium diversity. Replicated data generated from isoclonal Symbiodinium cultures showed that all genomes contained numerous, yet mostly rare, ITS 2 sequence variants. Pyrosequencing data were consistent with more traditional denaturing gradient gel electrophoresis ( DGGE ) approaches to the screening of ITS 2 PCR amplifications, where the most common sequences appeared as the most intense bands. Further, we developed an operational taxonomic unit ( OTU )‐based pipeline for Symbiodinium ITS 2 diversity typing to provisionally resolve ecologically discrete entities from intragenomic variation. A genetic distance cut‐off of 0.03 collapsed intragenomic ITS 2 variants of isoclonal cultures into single OTU s. When applied to the analysis of field‐collected coral samples, our analyses confirm that much of the commonly observed Symbiodinium ITS 2 diversity can be attributed to intragenomic variation. We conclude that by analysing Symbiodinium populations in an OTU ‐based framework, we can improve objectivity, comparability and simplicity when assessing ITS 2 diversity in field‐based studies.

Polyuridylylation and processing of transcripts from multiple gene minicircles in chloroplasts of the dinoflagellate Amphidinium carterae - Adrian C. Barbrook; Richard G. Dorrell; Jennifer Burrows; Lindsey J. Plenderleith; R. Ellen R. Nisbet; Christopher J. Howe (Plant Molecular Biology, 2012)

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Structural and kinetic studies of imidazole binding to two members of the cytochrome c 6 family reveal an important role for a conserved heme pocket residue - Badri S. Rajagopal; Michael T. Wilson; Derek S. Bendall; Christopher J. Howe; Jonathan A. R. Worrall (JBIC Journal of Biological Inorganic Chemistry, 2011)

The research potential of tissue from a cadaveric donor - Christopher Womack; Neil M. Gray; Lesley J. Howes; Michael D. Harris (Cell and Tissue Banking, 2002)